2022
DOI: 10.3390/ijms23137247
|View full text |Cite
|
Sign up to set email alerts
|

Gene Networks of Hyperglycemia, Diabetic Complications, and Human Proteins Targeted by SARS-CoV-2: What Is the Molecular Basis for Comorbidity?

Abstract: People with diabetes are more likely to have severe COVID-19 compared to the general population. Moreover, diabetes and COVID-19 demonstrate a certain parallelism in the mechanisms and organ damage. In this work, we applied bioinformatics analysis of associative molecular networks to identify key molecules and pathophysiological processes that determine SARS-CoV-2-induced disorders in patients with diabetes. Using text-mining-based approaches and ANDSystem as a bioinformatics tool, we reconstructed and matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 242 publications
0
4
0
Order By: Relevance
“…In ARDS due to other causes, higher ang-2 has been linked to the underlying pathogenesis of ARDS 31 . Ang-2 is normally downregulated by angiotensin-converting enzyme 2 (ACE2) 32 . Given that ACE2 is a receptor for SARS-CoV-2 entry in the host cells, leading to downregulation of ACE2 with ensuing endothelial dysfunction 33 , the ratio of ang-2/ang-1 is of particular relevance in COVID-19 induced ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…In ARDS due to other causes, higher ang-2 has been linked to the underlying pathogenesis of ARDS 31 . Ang-2 is normally downregulated by angiotensin-converting enzyme 2 (ACE2) 32 . Given that ACE2 is a receptor for SARS-CoV-2 entry in the host cells, leading to downregulation of ACE2 with ensuing endothelial dysfunction 33 , the ratio of ang-2/ang-1 is of particular relevance in COVID-19 induced ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Using gene network analysis, a prior study identified PLAT as a SARS-CoV-2 target and elucidated its potential involvement in COVID-19's inflammatory response, metabolism of reactive oxygen species, and immune response. (Saik and Klimontov, 2022). Wan et al conducted a large-scale genome-wide analysis of two COPD cohorts and obtained DNA methylation data for 27,578 CpG sites in 14,475 genes.…”
Section: Figurementioning
confidence: 99%
“…Studying genetic variants in populations is an important approach applied earlier for diabetes [21]. Olga Saik and Vadim Klimontov [22] considered the challenging problem of COVID-19 complications and comorbidity including diabetes. Using text-mining-based approaches and the ANDSystem [23,24] as a bioinformatics tool, the authors reconstructed and matched networks related to hyperglycemia, diabetic complications, insulin resistance and beta cell dysfunction with networks of SARS-CoV-2-targeted proteins.…”
mentioning
confidence: 99%